Susceptibility of heat shock protein 70.1-deficient C57BL/6 J, wild-type C57BL/6 J and A/J mice to Trypanosoma congolense infection - Nakamura, Y.; Naessens, Jan; Takata, M.; Taniguchi, T.; Sekikawa, K.; Gibson, John P.; Iraqi, F.A. (Springer, 2003)
The heat shock protein (HSP) 70.1 gene lies on mouse chromosome 17 among the candidates for Tir1, the major quantitative trait locus associated with response to Trypanosoma congolense infection. To evaluate whether the HSP70.1 gene is involved in the response, we compared the susceptibility of HSP70.1-deficient C57BL/6 J, resistant wild-type C57BL/6 J and susceptible A/J mice. No differences were observed between HSP70.1-deficient and wild-type C57BL/6 J mice in survival time, levels of parasitemia and anemia, suggesting that there is no involvement of the HSP70.1 gene in control of T. congolense infection. The course of infection was markedly different between A/J and C57BL/6 J mice. A/J mice showed a bi-phasic survival pattern, which seemed to be associated with two waves of high parasitemia, but developed only moderate anemia. C57BL/6 J mice controlled parasitemia well but developed severe anemia in the late stage of infection.